Peer Attachment, Fathering, Social Media Use and Perception of Premarital Sexual Attitude among Teenagers: Peer Attachment, Fathering, Social Media Use and Perception of Premarital Sexual Attitude among Teenagers - Yulina Eva Riany; Belinda Handayani (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2020)
This study aimed to analyze the links among peer attachment, fathering, social media use, and the perception of premarital sexual among adolescents. Two hundred and four high school (SMA) students and 114 Vocational High School (SMK) students voluntarily participated in this online survey. Results showed fathering was negatively associated with the perception of premarital sex among adolescents in which participants with positive experiences in fathering would report low score in perception of premarital sexual. On the other hand, social media use was significantly linked to the high score of perception of premarital sexual. Regression analysis indicated participants’ dating experience, lack of fathering experience and high social media use to be predictors for the perception of premarital sex among adolecscent.